Evaluation and management of Mullerian duct anomalies - Patel, Mittal D.; Vyas, Rupa C.; Shah, Sapana R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Development of the female genital tract is a complex embryogenesis including cell differentiation, migration, fusion, and canalization. Mullerian duct anomalies (MDA) are structural anomalies which occur due to defective embryogenesis of the Mullerian ducts, resulting in abnormalities of internal reproductive organs and ambiguity of the external genitalia. Other causes include deficiencies in steroidogenesis, signalling defects of WNT4 gene and TP63, receptor defects and genetic abnormalities. Methods: A prospective observational study was performed at our institute to observe the congenital anomalies of the female genital tract in our population and their clinical implication. Results: Most common anomaly observed was septate uterus followed by bicornuate uterus. Gynaecological complication: most common presenting symptom was primary amenorrhea followed by cyclical abdominal pain. Obstetric complication: women with Mullerian duct anomalies have a higher incidence of preterm labour, repeated first trimester spontaneous abortions, foetal malpresentations, and intrauterine foetal growth restriction. Hysterosalpingography (HSG) and ultrasonography (USG) are the primary tools to detect genital tract anomalies, Magnetic resonance imaging (MRI) being gold standard for detecting Mullerian duct anomalies. Conclusions: Mullerian duct anomalies can present with various obstetric and gynaecological complications. MRI is superior to other diagnostic modalities (HSG or USG) in establishing an accurate diagnosis and deciding further management options. Surgical approach used for correction of these anomalies is specific to the type of malformation and may vary in a specific group.